Examining the effect of reduced action capabilities on defensive anticipation in a 1-vs-1 task - Wilson, R.; Alder, D.; Dicks, M.; Poolton, J. (Science and Medicine in Football, 2021)
This study used small-sided games (SSGs) to induce fatigue and therefore, reduce the action capabilities of Varsity soccer players (n= 20). The aim was to examine the effect of compromised action capabilities on defensive movement response in a 1-vs-1 scenario. Action capabilities were assessed via countermovement jumps (CMJ), 5-m acceleration, 20-m sprint and a Change of Direction (COD) test. Defensive movement response was measured via a Soccer-Specific Anticipation Test (SSAT). Following SSGs, significant reductions were observed in jump (p=.04, d=.31), acceleration (p<.001, d=.98), and sprint (p<.001, d=.66) performance. Significantly, players tended to move earlier in the SSAT following SSGs (p=.049, d=.66). Furthermore, to examine the distinct effect of reductions in each action capability, players were categorised according to whether SSGs had a worthwhile change in CMJ, acceleration, sprint or COD performance. For each of the four measures, movements tended to be initiated earlier following SSGs, although pre-/post-SSGs differences were not significant (p =.08-.51), moderate to large effect sizes were shown (d=.56-.84). These findings intimate that compromised action capabilities influence the timing of the movement response of defensive players in 1-vs-1 situations.